2019
DOI: 10.1002/ijc.32659
|View full text |Cite
|
Sign up to set email alerts
|

Associations between calcium and magnesium intake and the risk of incident gastric cancer: A prospective cohort analysis of the National Institutes of Health‐American Association of Retired Persons (NIH‐AARP) Diet and Health Study

Abstract: Gastric cancer remains a leading cause of cancer‐related mortality. Identifying dietary and other modifiable disease determinants has important implications for risk attenuation in susceptible individuals. Our primary aim was to estimate the association between dietary and supplemental intakes of calcium and magnesium and the risk of incident gastric cancer. We conducted a prospective cohort analysis of the National Institutes of Health‐American Association of Retired Persons Diet and Health Study. We used Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
4
5
0
Order By: Relevance
“…This is in line with studies that established the signi cance of calcium intake, in particular, as a potential effect modi er of the association between calcium and diseases including gastrointestinal tract neoplasia (Hashemian et al 2015;Shah et al 2020aShah et al , 2020b. Increasing dietary calcium intake was associated with lower risk of oesophageal cancer (Hashemian et al 2015;Shah et al 2020aShah et al , 2020b. There seems to be inconsistent ndings on the relationship between serum calcium and risk of cancer in current literature.…”
Section: Discussionsupporting
confidence: 84%
“…This is in line with studies that established the signi cance of calcium intake, in particular, as a potential effect modi er of the association between calcium and diseases including gastrointestinal tract neoplasia (Hashemian et al 2015;Shah et al 2020aShah et al , 2020b. Increasing dietary calcium intake was associated with lower risk of oesophageal cancer (Hashemian et al 2015;Shah et al 2020aShah et al , 2020b. There seems to be inconsistent ndings on the relationship between serum calcium and risk of cancer in current literature.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, randomized clinical trials reported that calcium supplementation with doses (1200–2000 mg/day) for a period of more than 36 months reduced the risk of recurrent colorectal adenomas ( Fig. 2 (C) ), ( Shah et al, 2020 ).…”
Section: Resultsmentioning
confidence: 82%
“…There are scant data on the role of micronutrients in pancreatic cancer etiology, particularly data generated from prospective cohort studies. It has been reported that high intake of calcium and magnesium was associated with a reduced risk of other sites of gastrointestinal cancer (27,28). These observations suggest that intake of these minerals may also modulate the risk of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 88%